KONTEKSTUALISASI PEMBELAJARAN DENGAN OBJEK BIOLOGI, EFEKNYA PADA KETERAMPILAN MAHASISWA MERENCANAKAN PEMBELAJARAN - Suhirman, Suhirman (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2019)
[Title: Contextualization of Learning with Biological Objects, Its Effect on Student Skills Planning Learning]. This study aims to describe the impact of the contextualization of learning with biological objects on learning planning skills. This type of quantitative descriptive research with quasi-experimental methods, research design posttest-only control design. Cluster random sampling is carried out in determining the research sample consisting of 80 experimental and control classes in the sixth semester of the Department of Natural Sciences of Biology, FTK UIN Mataram. Student skills planning data for learning are collected with a performance test instrument then analyzed by t statistics. The results showed that the average value of the experimental class 65.70 was lower than the control class 69.13 (p = 0.143> 0.05, meaning that it did not differ significantly. Thus the contextualization of learning with biological objects did not have a significant impact on student skills in planning to learn. The planning of learning biology can be done by students even though they are not dealing directly with the real object of biology.